Performance Analysis of 120 kWp Grid-Connected Rooftop Solar Photovoltaic System in Central Java - Mukhamad Faeshol Umam; Ferry Purwo Saputro; Sesi Selia; Amrullah Farad Sunaryo; Umi Yuliatin; Muhammad Rizqi Al Asy’ari (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2021)
This study examines the performance of a solar power plant with a total capacity of 125 KWp, which operates for one year in Blora, Central Java. The ability of this power plant is a total of PV modules with 20 kWp, ten kWp, and five kWp capacities spread across eight locations. The annual performance of the rooftop solar power plant is measured automatically by the converter installed in each module. The resulting data from inverters are compared to the meteorological conditions from the meteorological agency. This research will investigate the influence of climate on the power generated, the efficiency of the equipment in a power plant, and the effect of pseudo motion of the sun. It was found that there were variations in energy output throughout the year, and it was concluded that the maximum annual energy was produced in July-August. In addition to weather, other factors need to be investigated further to determine the causes of variations in solar PV output.